Tuning the microstructure of the Pt layers grown on Al2O3 (0001) by different sputtering methods. (15th March 2021) - Yıldırım, Oğuz; Borzì, Aurelio; Falub, Claudiu V.; Rohrmann, Hartmut; Jaeger, Dominik; Rechsteiner, Marco; Schneider, Daniel; Neels, Antonia; Hug, Hans J.; Marioni, M.A.
Graphical abstract: Abstract: High-quality epitaxial Pt films are usually grown by molecular beam evaporation (MBE) techniques, where the deposited atoms reach the substrate with typical thermal energies. To obtain a good epitaxial growth, the substrate is kept at elevated temperatures ranging between few hundred to thousand degrees. While the epitaxial quality improves at higher substrate temperatures, above a critical temperature Volmer-Weber growth mode starts and causes a rough film morphology. Here, we use a new type of facing target cathode (FTC) to grow Pt onto Al 2 O 3 (0001) substrates. In contrast to conventional sputtering sources, FTC sources provide adatoms with lower kinetic energies, but higher growth rates compared to MBE. In this study, the crystal structure of Pt films is compared for different substrate temperatures. Using FTC, flat Pt films with low strain and a morphology that is either nanocrystalline or highly epitaxial could be grown through proper choice of substrate temperature.